Optimalisasi Alat Monitoring Tetes Infus Kristaloid Berbasis Mikrokontroler ATMega328 - Mokodompit, Hudi Prayoga; Asruddin, Asruddin; Abdillah, Junindo (FIKOM Universitas Bung Karno, 2023)
In the medical world, supervision of intravenous devices is a priority and the main one to ensure proper and measurable fluid delivery to patients. This research focuses on the development of a crystalloid infusion drip monitoring device using a microcontroller. The background of this research arises from the need for a device that is able to monitor drip infusions automatically, reduce the workload of medical personnel and increase patient safety. The methods used in this study include designing, manufacturing, and testing on tools. Photodiode sensors are selected as the main component in detecting drops of crystalloid liquid. This tool is designed to optimize other supporting sensors to be integrated as instruction modules in counting infusion fluid drops. The application of microcontroller technology in affordable infusion monitoring devices has not been widely adopted in medical practice. This research is driven by the need for reliable monitoring tools in a fast-paced medical environment and requires precision. The results of this study showed that the developed tool succeeded in optimizing the function of the photodiode sensor in counting drops of 99% crystalloid liquid produced accurately. This tool is able to operate in accordance with its original purpose, namely as a monitoring tool as well as a reminder for patient safety. The conclusion is that this microcontroller-based crystalloid infusion drip monitoring device is an innovation and good practice in the medical field. This tool not only increases efficiency in infusion monitoring but also provides additional safety for patients.